Implementation of the ESP-NOW Protocol in a Multi-Sensor-Based Control System Using ESP8266 and ESP32 - Marsinta Uli Sinurat; Ahmad Dani; M. Rizky Syahputra (Bahasa Indonesia, 2026)
The rapid development of the Internet of Things (IoT) has increased the demand for wireless communication systems that are fast, efficient, and independent of internet network infrastructure. This study aims to implement the ESP-NOW protocol in a multi-sensor monitoring system using ESP32 as the data transmitter and ESP8266 as the data receiver. The system was designed to acquire temperature and humidity data using a DHT11 sensor and distance data using an HC-SR04 sensor, which were then transmitted in real time through ESP-NOW communication. On the receiver side, the data were displayed on a 16×2 LCD and Serial Monitor, while packet loss was calculated using the sequence number method. An experimental approach was employed to evaluate communication performance based on temperature, humidity, distance, received packets, lost packets, and packet loss percentage. The results showed that the DHT11 sensor produced an average temperature of 29.82°C and an average humidity of 75.1%, while the HC-SR04 sensor achieved a measurement error of less than 2%. Communication testing was conducted over five cycles with 100 samples per cycle. The first three cycles recorded 0% packet loss, whereas the fourth and fifth cycles experienced packet losses of 32.34% and 62.12%, respectively. The average packet loss obtained was 18.89%. The findings indicate that ESP-NOW is capable of supporting real-time multi-sensor data communication without requiring an access point or internet connection, although communication quality is influenced by distance, physical obstacles, and signal interference. The developed system demonstrates potential for deployment in various IoT-based monitoring and automation applications.